Effect of organic and inorganic regimes on growth, production and quality characteristics of cauliflower - Hussain, Zawar; Alam, Mehboob; Ullah, Izhar; Ahmad, Imran; Sajid, Muhammad; Alam, Intikhab; Rehman, Attiq Ur; Shah, Muhammad Azhar; Asif, Muhammad (Innovative Scientific Information & Services Network, 2020)
Increasing crop yield through balanced use of fertilizers in combination with organic acids is a need of the time to limit the use of costly chemical fertilizers as well as to minimize the environmental pollution in Pakistan.This trial aimed to investigate the benefits of organic and inorganic regimes application on growth, yield and quality of cauliflower. In this study, organic (Farmyard manure (FYM), Poultry manure (PM), Spent mushroom Compost (SMC) at the rate of (15:3:6 t ha-1), inorganic (NPK @ 100:60:60 kg ha1) regimes and Cauliflower cultivars (Kohat local, Hollywood, Lucky, White beauty and Pearl) were used. The organic regime showed highest value for number of leaves plant-1, leaf area, chlorophyll content, plant height, curd diameter, curd weight, curd dry matter content and total yield of the cauliflower. Regarding cultivars, the minimum days to germination, maximum number of leaves plant-1, chlorophyll content, curd diameter, curd weight, curd dry matter content and total yield were recorded in cultivar Lucky. While cultivar White beauty showed maximum leaf area, plant height and curd pH. From the results it is concluded that cultivar Lucky performed well in organic regimes and recommended for better quality and high yield production in Peshawar valley.
Keywords: Soil fertility management; Nitrogenous fertilizer; Caleus; Disease resistance; Composts; Brassicaceae